A longitudinal study of disease incidence and case fatality risks on smallholder dairy farms in coastal Kenya - Maloo, S.H.; Rowlands, G.J.; Thorpe, W.R.; Gettinby, George; Perry, Brian D. (Elsevier, 2001)
A longitudinal study was carried out in the coastal lowlands coconut¯cassava agro-ecological zone of Kaloleni Division, Coast Province, Kenya between June 1990 and December 1991 to estimate disease incidence and cause-specific case-fatality risk in an average of 120 cattle in 26 small-holder dairy herds kept in two grazing-management systems. East Coast fever (ECF) was the predominant disease diagnosed; the mean monthly incidence rate was 2.5 and 6.9% in animals 18 months of age under stall-fed and herded-grazing systems, respectively. In cattle >18 months of age, the monthly incidence rate was <1%. The 6-month ECF incidence rate was 20±8% (S.E.) in the stall-feeding system compared with 39±7% in the herded-grazing systems. There was a gradual increase in antibody prevalence with age to over 90% in cattle over 18 months of age in herded-grazing systems, whilst less than a third of cattle in the stall-feeding systems were sero-positive at any age. Overall accumulated mortality to 18 months of age was estimated to be 56%. Annual mortality in cattle >18 months averaged 9%. Cattle managed in the herded-grazing system had a 60% higher mortality, although not significantly so, than those fed in stalls. Deaths due to ECF accounted for over two-thirds of the deaths. ECF was then the major disease constraint to small-holder dairy production in the coconut zone of coastal Kenya. Clinical cases occur the whole year round (especially in young stock) ¯¯ despite apparent tick control, and in both herded-grazing and stall-feeding system.